Soil Mediated Allelopathic Effect of Echinochloa colona on Germination and Seedling Growth of Zea mays - MAJEED,M.A. (2018)
ABSTRACT: The soil mediated allelopathic effect of Echinochloa colona (L.) Link (jungle rice) was investigated on seed germination and seedling growth of Zea mays L. (maize). The experiment was conducted in the Agronomy farm of the University of Agriculture, Faisalabad, Pakistan. This study investigated the effect of different concentrations (1, 2, 3, 4 and 5% on w/w basis) of soil incorporated E. colona plant residues on emergence and seedling growth of maize and compared them with residue free soil (control). The results revealed the significant increase with soil incorporated E. colona residues in maize seedling growth till 2% E. colona plant residues, and an inhibitory effect was noticed over 2% E. colona plant residues in comparison to the control treatment. There was maximum reduction in emergence percentage, root and shoot lengths, root and shoot dry weights and seedling vigor index of maize seedlings at 5% E. colona plant residues. Quercetin, ferulic acid, sinapic acid, syringic acid, cinnamic acid, m-coumaric acid were identified as water soluble phenolic in water extract of E. colona.